Peran dan Kendala Jurnalis dalam Pemberitaan Deforestasi di Aceh: (Studi Terhadap Wartawan Harian Serambi Indonesia Tahun 2019) - Syukri Syamaun (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This illegal logging practice occurs in almost all districts in Aceh. The mass media should be part of the socialization of various illegal logging cases that have occurred in Aceh. News Serambi Indonesia is able to carry out an in-depth and comprehensive investigation of illegal logging in Aceh. Serambi Indonesia must be able to expose the involvement of the